Cover Image, Volume 31, Issue 4. (15th March 2018) - Zhang, Yue; Taub, Edward; Salibi, Nouha; Uswatte, Gitendra; Maudsley, Andrew A.; Sheriff, Sulaiman; Womble, Brent; Mark, Victor W.; Knight, David C.
Abstract : The cover image, by Yue Zhang et al., is based on the Research Article Comparison of reproducibility of single voxel spectroscopy and whole‐brain magnetic resonance spectroscopy imaging at 3T, DOI: 10.1002/nbm.3898 .